2023
DOI: 10.3390/biom13091338
|View full text |Cite
|
Sign up to set email alerts
|

Does SARS-CoV-2 Induce IgG4 Synthesis to Evade the Immune System?

Alberto Rubio-Casillas,
Elrashdy Redwan,
Vladimir Uversky

Abstract: SARS-CoV-2, the virus that causes the COVID-19 disease, has been shown to cause immune suppression in certain individuals. This can manifest as a reduced ability of the host’s immune system to effectively control the infection. Studies have reported that patients with COVID-19 can exhibit a decline in white blood cell counts, including natural killer cells and T cells, which are integral components of the immune system’s response to viral pathogens. These cells play critical roles in the immune response to vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…The difference in IgG peak levels between the second and third doses could be influenced by factors such as the age distribution of vaccine recipients, the timing of sampling, and the method of measurement. Interestingly, recent studies demonstrated that the IgG4 subclass antibody was upregulated in repeated vaccination of SARS-CoV-2 mRNA [ 37 , 38 ], indicating the IgG4 class switch mechanism for immune regulation [ 39 , 40 ]. Nevertheless, it is important to note that vaccine effectiveness against Delta variants increased significantly after the third vaccination [ 34 , 35 , 36 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in IgG peak levels between the second and third doses could be influenced by factors such as the age distribution of vaccine recipients, the timing of sampling, and the method of measurement. Interestingly, recent studies demonstrated that the IgG4 subclass antibody was upregulated in repeated vaccination of SARS-CoV-2 mRNA [ 37 , 38 ], indicating the IgG4 class switch mechanism for immune regulation [ 39 , 40 ]. Nevertheless, it is important to note that vaccine effectiveness against Delta variants increased significantly after the third vaccination [ 34 , 35 , 36 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 may employ evasion mechanisms to avoid immune surveillance and attack, including inhibition of interferon (IFN) synthesis, disruption of Ag presentation, evasion of Ab through nanotube construction, and induction of lymphopenia through syncytial generation [ 15 ]. Evidence indicates that changes in IFN-γ level dynamics after the booster dose are less pronounced than the humoral dynamics.…”
Section: Recent Scientific Debatesmentioning
confidence: 99%
“…Furthermore, individuals who have received three doses of Comirnaty Original may experience a reduction in Ab-mediated phagocytic activity and complement deposition. This could potentially increase the risk of other opportunistic infections [ 15 , 22 , 23 , 24 ].…”
Section: Recent Scientific Debatesmentioning
confidence: 99%
See 2 more Smart Citations